2021
DOI: 10.1111/1751-7915.13967
|View full text |Cite
|
Sign up to set email alerts
|

Efficient markerless integration of genes in the chromosome of probiotic E. coli Nissle 1917 by bacterial conjugation

Abstract: Summary The probiotic strain Escherichia coli Nissle 1917 (EcN) is a common bacterial chassis in synthetic biology developments for therapeutic applications given its long track record of safe administration in humans. Chromosomal integration of the genes of interest (GOIs) in the engineered bacterium offers significant advantages in genetic stability and to control gene dose, but common methodologies relying on the transformation of EcN are inefficient. In this work, we imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 92 publications
(134 reference statements)
0
8
0
Order By: Relevance
“…The EcN native tolC operon bears 4 promoters, which we also targeted for removal on the 5′ end of the operon to ensure minimal read through driven by the endogenous tolC operon promoters as well as the tolC ORF seamlessly removed (Figure ). In order to determine if EcN would allow for sufficient recombination of foreign introduced donor DNA incorporated into the EcN genome, we utilized a modified gene integration protocol of Yang et al for the first time in the enteric probiotic, EcN. , As shown in Figure S9−S11S9–S11, Yang et al . largely bases their system off of the recombinase driven Datsenko et al protocol except that donor DNA on a separate donor plasmid is flanked by a FRT and endonuclease recognition site, I-Sce-I . , I-Sce-I is an extremely rare recognition site in bacterial genomes, originally from S.cerevisae .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EcN native tolC operon bears 4 promoters, which we also targeted for removal on the 5′ end of the operon to ensure minimal read through driven by the endogenous tolC operon promoters as well as the tolC ORF seamlessly removed (Figure ). In order to determine if EcN would allow for sufficient recombination of foreign introduced donor DNA incorporated into the EcN genome, we utilized a modified gene integration protocol of Yang et al for the first time in the enteric probiotic, EcN. , As shown in Figure S9−S11S9–S11, Yang et al . largely bases their system off of the recombinase driven Datsenko et al protocol except that donor DNA on a separate donor plasmid is flanked by a FRT and endonuclease recognition site, I-Sce-I . , I-Sce-I is an extremely rare recognition site in bacterial genomes, originally from S.cerevisae .…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine if EcN would allow for sufficient recombination of foreign introduced donor DNA incorporated into the EcN genome, we utilized a modified gene integration protocol of Yang et al 52 for the first time in the enteric probiotic, EcN. 51,52 As shown in Figure S9 In Figure 5, the density plots a clear positive population shift with increasing concentration of cortisol is observed with 31% and 62% of the whole cell cortisol biosensor responding to 1 μM and 2 μM respectively. Figure 5 shows a kinetic study performed with the ΔtolC:lysRsf GFP EcN strain, wherein flow cytometry was used to follow the engineered strain treated with a saturating dose of 50 μM of cortisol.…”
Section: Targeted Integration Of the Lysr Mediated Glucocorticoid Sen...mentioning
confidence: 99%
“…The results indicated that the good anchoring ability and penetration properties of microrobots (Figure d). It should be noted that bacteria invasion to cells is closely associated with flagella, which sense the cell surface and determine the optimal location for invasion. We then tested the ROS level in CT26 cells cocultured with the microrobots under the AMF. Figure e showed that the EcN@MNP + MH group significantly elevated the intracellular ROS level as compared to the MNP + MH group.…”
Section: Resultsmentioning
confidence: 99%
“…[19] Up to now, EcN has become one of the most popular probiotic chassis for developing living therapeutics in pathogenic infections, [21] metabolic regulation, [16] GI tract inflammations, [15] and antitumor treatments. [22] Nowadays, some EcN-based genetic engineering strategies, including genome engineering (e.g., Lambda-Red recombination, [23] integrase-based site-specific recombination, [24] and CRISPR-Cas-based gene editing technologies), [25][26][27] cryptic plasmid engineering, [25][26][27] and chassis modification, [24,28] have been designed, built, and tested. However, the genetic engineering toolbox of EcN can be further expanded in other fields due to its unique properties.…”
Section: Introductionmentioning
confidence: 99%